2005
DOI: 10.2337/diabetes.54.9.2802
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Polymorphism Predicts 30-Day Mortality and Heart Failure in Patients With Diabetes and Acute Myocardial Infarction

Abstract: Patients with diabetes presenting with acute myocardial infarction (AMI) have an increased rate of death and heart failure. Patients with diabetes homozygous for the haptoglobin (Hp) 1 allele (Hp 1-1) develop fewer vascular complications. We tested the hypothesis that Hp type is related to the outcome of patients with diabetes presenting with AMI. We prospectively assessed the relationship between Hp type and 30-day mortality and heart failure in 1,437 patients with AMI (506 with diabetes). Multivariate logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 25 publications
5
70
2
Order By: Relevance
“…An intermediate risk was found in individuals with the Hp-2-1 genotype (heterozygote). 55,[57][58][59] Remarkably, these studies have demonstrated that the cardiovascular risk of Hp-1-1 individuals with DM is not significantly different from that found in individuals without DM; apparently, the Hp-1-1 genotype mitigates the effect of DM on the development of cardiovascular disease. The mechanisms responsible for the increased importance of the Hp genotype on the development of diabetic cardiovascular disease may be related to the increased development of plaque neovessels in the diabetic state and the increased propensity of these neovessels to rupture and hemorrhage.…”
Section: Free Hemoglobin Haptoglobin and Macrophage Activationmentioning
confidence: 90%
“…An intermediate risk was found in individuals with the Hp-2-1 genotype (heterozygote). 55,[57][58][59] Remarkably, these studies have demonstrated that the cardiovascular risk of Hp-1-1 individuals with DM is not significantly different from that found in individuals without DM; apparently, the Hp-1-1 genotype mitigates the effect of DM on the development of cardiovascular disease. The mechanisms responsible for the increased importance of the Hp genotype on the development of diabetic cardiovascular disease may be related to the increased development of plaque neovessels in the diabetic state and the increased propensity of these neovessels to rupture and hemorrhage.…”
Section: Free Hemoglobin Haptoglobin and Macrophage Activationmentioning
confidence: 90%
“…They found that diabetic patients with the Hp1-1 phenotype had smaller infarction sizes, whereas patients with Hp2-1 and Hp2-2 phenotypes sustained larger infarctions and consequently had a higher rate of heart failure and mortality 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Suleiman et al 19 demonstrated that the Hp phenotype is an important predictor of 30-day mortality and heart failure among individuals with diabetes and acute myocardial infarction. They found that diabetic patients with the Hp1-1 phenotype had smaller infarction sizes, whereas patients with Hp2-1 and Hp2-2 phenotypes sustained larger infarctions and consequently had a higher rate of heart failure and mortality 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations